2020
DOI: 10.5152/j.aott.2020.02.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich plasma and platelet-rich fibrin matrix on healing of vertical meniscal tears in a rabbit model

Abstract: The role of the platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio in the prediction of length and cost of hospital stay in patients with infected diabetic foot ulcers: A retrospective comparative study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This model thus may provide a well-defined test bed for the assessment of novel repair approaches for these types of tears. Indeed, many groups have used a vertical longitudinal tear during ex vivo and large-animal assessment of biologic, 38 , 74 , 78 , 83 scaffold-based, 5 , 62 , 65 or surgical repair 2 , 4 , 12 , 16 , 48 , 68 strategies. The stability of this defect and lack of healing observed in the meniscus itself indicate its utility for such studies.…”
Section: Discussionmentioning
confidence: 99%
“…This model thus may provide a well-defined test bed for the assessment of novel repair approaches for these types of tears. Indeed, many groups have used a vertical longitudinal tear during ex vivo and large-animal assessment of biologic, 38 , 74 , 78 , 83 scaffold-based, 5 , 62 , 65 or surgical repair 2 , 4 , 12 , 16 , 48 , 68 strategies. The stability of this defect and lack of healing observed in the meniscus itself indicate its utility for such studies.…”
Section: Discussionmentioning
confidence: 99%
“…PRP has shown the capacity to inhibit inflammation and improve cartilage tissue regeneration by promoting the synthesis of cartilage matrix, increasing cell growth and migration, and inducing phenotype changes [133,153]. In the field of meniscus tissue engineering (MTE), PRP has been incorporated into various hydrogel systems and has demonstrated high potential for meniscus repair [132,133,[155][156][157][158][159]. It is worth mentioning that PRP contains fibrinogen, which can be activated by thrombin and Ca 2+ to form a hydrogel.…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%
“…PRF enhanced the synthesis and deposition of ECM by cultured meniscocytes, which were evaluated both morphologically and histologically [87]. Kurnaz et al concluded that PRP and PRF matrix augmentation on vertical meniscal tears in a rabbit model resulted in early recovery and enhanced repair of meniscus tissue [88]. The role of PRF in terms of healing and regeneration of meniscus tissue needs to be explored.…”
Section: Meniscal Injuriesmentioning
confidence: 99%